TINDAK TUTUR DAN PELANGGARAN MAKSIM PERCAKAPAN PADA NOVEL HARRY POTTER AND THE SORCERER’S STONE - Ida Ayu Panuntun (LPPM Universitas Pekalongan, 2012)
One of the most important aspects of the language use is in the people’s implicature that can be shown in the conversation. As in fact, many students do not understand the conversational maxims that cause the implicature. Based on its background, this study uses a novel entitled “Harry Potter and the Sorcerer’s Stone” to enrich the understanding of conversational maxims. This study has two purposes. The first is to identify the maxims which flout the cooperative principle in term of meanings. The second is to identity the speech act of each implicature. The method used in this study was descriptive qualitative with cooperative principle analysis approach. The objects of the study were the conversations. The findings show that there are 47.4% conversations which flout quaqntity maxim; 13.2% conversations which flout quality maxim; 31.6% conversations which flout relevance maxim and 7.9% conversations which flout manner maxim. Meanwhile the next finding related to the speech act. There are expressive, directive and representative. It is suggested that these findings can be used as a recommendation for researchers to use other novels as the object of the study and other point of view, such as to describe and explain the level of difficulty in the conversational maxims. Keywords: speech act, cooperative principle, novel